Eligibility for antiviral therapy and treatment uptake in chronic hepatitis B patients referred to a European tertiary care center. Issue 3 (25th March 2023) - Jachs, Mathias; Sauberer, Raphael; Stiegler, Alexander; Dechêne, Anton; Tazreiter, Raphael; Hartl, Lukas; Bauer, David; Balcar, Lorenz; Strassl, Robert; Mandorfer, Mattias; Trauner, Michael; Munda, Petra; et al.
Abstract: Background and Aims: Treatment indications for chronic hepatitis B (CHB) differ among recommendations by European Association for the Study of the Liver (EASL), American Association for the Study of Liver Diseases (AASLD) and World Health Organization (WHO). We aimed to assess treatment eligibility and linkage to therapy at a large tertiary care center. Methods: All CHB patients who were evaluated for treatment at the Vienna General Hospital between January 2010 and December 2020 were retrospectively included. Clinical, virological, and long‐term treatment efficacy data were analyzed. Results: A total of 751 CHB patients were included (53.3% male; median age: 39.5 years; HBeAg‐positive: 10.8%). The median Hepatitis B Virus (HBV)‐DNA and HBsAg levels were 569 (68–11, 750) IU/mL and 3467.65 (620.05–11, 935.43) IU/mL, respectively. Overall, 9.2% of patients had severe fibrosis/cirrhosis, and 5.7% were coinfected with hepatitis D virus (HDV), which was highly prevalent in cirrhosis. According to the recent EASL nomenclature, 3.2% of patients had HBeAg‐positive chronic infection, 7.6% had HBeAg‐positive chronic hepatitis, 58.9% had HBeAg‐negative chronic infection, and 30.4% had HBeAg‐negative chronic hepatitis. At the time of evaluation, 36.4% had HBV‐DNA >2000 IU/mL, and 37.3% showed alanine aminotransferase >40 U/L. Ultimately, 26.9% (EASL), 29.0% (AASLD) and 23.4% (WHO) met the treatment criteria. Treatment was initiated in most patients, mainly with tenofovir (61.8%) or entecavir (34.9%). Treatment efficiently suppressed HBV‐DNA in all patients; however, HBsAg loss was observed only in 2.8% at 5 years of therapy. Conclusions: Severe fibrosis/cirrhosis was found in 9.2% of CHB patients at presentation, and 23.4%–29.5% met current treatment recommendations with a high treatment uptake of 79.8%–89.2% among eligible patients. Abstract :